Bioactivity and Bioaccessibility of Bioactive Compounds in Gastrointestinal Digestion of Tomato Bagasse Extracts - Coelho, Marta (2022)
Funding: The authors would like to thank the CCTI group that kindly provided the samples. Also to thank to project Co-promoção nº 016403, “MULTIBIOREFINERY”, supported by Programa Operacional Competitividade e Internacionalização and by Programa Operacional Regional de Lisboa, in its component FEDER, and by Fundação para a Ciência e Tecnologia, byprojects UID/Multi/50016/2020 and UIDB/04469/2020 administrated by FCT, and by the I&D&I AgriFood XXI project (NORTE-01-0145-FEDER-000004) co-funded by the European Regional Development Fund under the scope of Norte2020 (Programa Operacional Regional do Norte 2014/2020) and BioTecNorte operation (NORTE-01-0145-FEDER-000004) funded by the European Regional Development Fund under the scope of Norte2020-Programa Operacional Regional do Norte. Furthermore, the author Marta Coelho would like to acknowledge FCT for your PhD grant with the reference [grant number SFRH/BD/111884/2015].